The effectiveness of the promotional tools used by RTM in enhancing viewers' interest towards RTM TV channels and programs / Muhammad Hafiz Mahmood (Faculty of Business Management, 2006)
Every organization needs to market its products or services provided by them. As well for RTM. RTM also market their products and services but public seems to have less interest with them. Public are aware about RTM TV channels and programs but they does not have interest towards the TV channels and programs. It seems that the effectiveness of the promotional tools used by RTM are ineffective in enhancing viewers' interest towards Its TV channels and programs. In conducting this research, exploratory research has been used. This is to give more understanding and can define the problem more precisely. For the data collection, sets of questionnaire were distributed in the area of Klang Valley. This is because for the population and sample of the research, 65 TV viewers in the Klang Valley area have been chose. From the finding, most of the respondents failed to get the message send by RTM using the current promotional tools. For the overall conclusion, it seems that the promotional tools used by RTM are ineffective and its failed to enhance viewers' interest towards RTM TV channels and programs.